INFLUENCE OF CORN AND SOYBEAN PRICES ON BROILERS PRICES - Tekić, Dragana; Šarac, Veljko; Mutavdžić, Beba; Vukelić, Nataša; Novakovic, Tihomir; Milić, Dragan; Miljatović, Aleksandar (Journal on Processing and Energy in Agriculture, 2024)
Given the crucial role of corn and soybeans in formulating poultry feed, this research delves into the interplay of prices between broilers chickens, corn, and soybeans. The primary objective of this study is to ascertain the influence of the previous year's corn and soybean prices on the current-year broilers chicken prices, employing a multiple linear regression model. The findings of the regression model reveal that an increase in the prices of corn and soybeans has a positive correlation with broilers prices. In simpler terms, as the prices of these two essential feed components rise in the previous year, a corresponding increase in broilers prices is anticipated in the current year. It's worth highlighting that the statistical analysis identifies only the influence of corn as statistically significant, while the impact of soybeans is deemed statistically non-significant. An increase in the price of corn in the previous year by 1 dinar will cause an increase in the price of broilerss by 3,766 dinars/kilogram in the current year.
Keywords: price, corn, soybean, broilers, regression analysis